Pembinaan Akhlak Anak Usia Dini Melalui Metode Sentra Imtaq - Ratna (STAI Kuala Kapuas, 2024)
Every human being is born in a state of nature and has a clean soul, but the process of development is influenced by environmental factors and also education, therefore it is important to educate and instill noble morals from an early age. The aim, of course, is to optimize the child's natural potential, one of which is moral potential, therefore moral development in early childhood needs to be carried out optimally. The imtaq center is one of the centers in early childhood education which aims to support the moral development of early childhood. The results of this research show that the morals of early childhood which are fostered through the IMTAQ center method are divided into morals towards Allah, morals towards fellow humans, and morals towards the environment. circle, the activities carried out are giving advice, telling stories, watching videos, through the rules of the game at the imtaq center, playing activities with supporting play equipment at the imtaq center, as well as providing support while the child is at the imtaq center. So that by developing morals at an early age through the imtaq center method, children become accustomed to doing good or positive things, such as children starting to get used to saying hello when entering a room, praying before and after doing something, and performing prayers without having to be asked again, as well as showing good behavior. praise for his teachers and friends.